Analisis Ketimpangan Distribusi Tenaga Kesehatan dan Fasilitas terhadap Akses Kesehatan Berkeadilan : Literatur Review - Budiman abd. Rauf; Andiansyah Yusuf Tunasly; Suraiyah; Arifandi; Suci Ismawati; Abdul Kadri (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
The unequal distribution of health workforce and healthcare facilities remains a major challenge in health systems, particularly in countries with vast and diverse geographical characteristics such as Indonesia. This study aims to analyze the inequality in the distribution of health workers and healthcare facilities and its implications for equitable access to healthcare services. The study employs a literature review method with a descriptive approach based on secondary data obtained from official publications and national and international scientific articles published between 2020 and 2026. Data were collected through documentation techniques, while data analysis was conducted using qualitative descriptive methods through the synthesis of previous research findings. The results indicate that the distribution of health workers and healthcare facilities is still concentrated in urban areas and economic centers, while rural, remote, and underdeveloped regions experience significant limitations in health resources. This inequality is influenced by economic factors, infrastructure disparities, policy limitations, and market mechanisms in healthcare provision that tend to prioritize efficiency over equity. The impacts include limited access to basic healthcare services, increased referral rates to higher-level healthcare facilities, and disparities in health outcomes across regions. Scientifically, this study finds that unequal distribution creates a mismatch between healthcare needs and resource availability (spatial mismatch), leading to inequity in healthcare access. This condition highlights that equitable distribution of health workforce is a key determinant in achieving fair access to healthcare services. Therefore, data-driven policies, strengthened incentives for health workers in remote areas, and integration between planning and health budgeting are essential to improve the effectiveness of resource distribution. The findings are expected to contribute to the development of more equitable, efficient, and sustainable health policies.